PENGARUH PEMANFAATAN BOKASHI FESES SAPI TERHADAP PERTUMBUHAN SORGUM VARIETAS KAWALI - Imban, Susisusanty; Rumambi, A; Malalantang, S S (ZOOTEC, 2017)
ABSTRACT UTILIZATION EFFECT OF CATTLE FECES BOKASHI ON GROWTH OF Kawali SORGHUM VARIETY . The Research about effect of utilization cow manure on growth of sorghum variety kawali has done. The aim of this research is to obtain data and determine the effect of utilization cow manure mixed with EM4 on growth of sorghum variety kawali. This study was conducted using a completely randomized design (CRD) which consists of 4 treatments and 5 replicates in each treatment. The treatments were divided into plots of the experimental unit without fertilizer (P0), the plot using organic fertilizer of 4 kg/6 m2 (P1), plot using organic fertilizer of 8 kg/6 m2 (P2), and plot using organic fertilizer of 12 kg/6 m2 (P3). The variables measured in this study were plant height, number of leaves and leaf width. The HSD test indicated that at high treatment plants showed that treatments between P3 and P0 and between P3 and P1 were highly significant. However, treatments between P3 and P2 showed no significant difference. In the treatments of advanced test HSD indicated also that number of leaves between P3 and P0 showed highly significant, but between P3 and P1, and between P3 and P2 showed no difference. In the treatment of wide leaves using HSD test showed that treatment between P3 and P0 was highly significant, but those between P3 and P1 and between P3 and P2 showed no difference. Statistical analysis showed that treatment using cattle feces bokashi as the organic fertilizer of 12 kg/ 6 m2 (P3) produced high significant influence on plant height, leaf number, and leaf width. Based on this research it can be concluded that cattle feces bokashi as the organic fertilizer up to 12 kg /plot of 6 m2 produced the best effect on plant height, leaf number, and leaf width of kawali sorghum variety. Key words: Sorgum, growt, Cattle feces bokashi,EM4.